China’s Export Growth and the China Safeguard : Threats to the World Trading System? - Bown, Chad P.; Crowley, Meredith A. (2012)
Is there evidence from China's pre-WTO accession period that newly imposed U.S. or EU import restrictions deflect Chinese exports to third markets? The authors examine this question by drawing on a newly constructed data set of U.S. and EU product-level import restrictions on Chinese trade imposed between 1992 and 2001 and estimate their impact on Chinese exports to 38 alternative markets. There is no systematic evidence that the import restrictions imposed during this period resulted in Chinese exports surging to such alternate destinations. To the contrary, there is weak evidence of a chilling effect on China's exports to third markets.